Computed tomography-guided additive manufacturing of Personalized Absorbable Gastrointestinal Stents for intestinal fistulae and perforations. (January 2020) - Fathi, Parinaz; Capron, Gweneviere; Tripathi, Indu; Misra, Santosh; Ostadhossein, Fatemeh; Selmic, Laura; Rowitz, Blair; Pan, Dipanjan
Abstract: Small bowel perforations and obstructions are relatively frequent surgical emergencies, are potentially life-threatening, and have multiple etiologies. In general, treatment requires urgent surgical repair or resection and at times can lead to further complications. Stents may be used to help with healing intestinal perforations but use is limited as currently available stents are non-absorbable, are manufactured in a narrow size range, and/or are limited to usage in locations that are accessible for endoscopic removal post-healing. The use of 3D-printed bioresorbable polymeric stents will provide patients with a stent that can prevent leakage, is tailored specifically to their geometry, and will be usable within the small bowel, which is not amenable to endoscopic stent placement. This work focused on the rapid manufacturing of gastrointestinal stents composed of a polycaprolactone-polydioxanone (PCL-PDO) composite. Dynamic Mechanical Analysis (DMA) tests were conducted to separately analyze the effects of composition, the filament formation process, and physiological temperature on the PCL-PDO material properties. The proposed stent design was then modeled using computer-aided design, and Finite Element Analysis (FEA) was used to simulate the effects of physiologically relevant forces on stent integrity. The presence of hydrolysable ester bonds was confirmed using FT-IR spectroscopy. In vitro studies were used to evaluate the biocompatibility of the polymer composite. Further analyses were conducted through stent placement in ex vivo pig intestines. PCL-PDO stents were then 3D-printed and placed in vivo in a pig model. Graphical abstract: Image 1